Bone Marrow-Derived Endothelial Progenitor Cells Reduce Recurrent Miscarriage in Gestation. Issue 12 (December 2016) - Kanki1, Kazuyoshi; Ii, Masaaki; Terai, Yoshito; Ohmichi, Masahide; Asahi, Michio
Bone marrow-derived endothelial progenitor cells (EPCs) have been shown to contribute to not only angiogenesis in ischemic tissue but also neovascularization in uterine endometrium formation. Reduced neovascularization and elevation of serum soluble Flt1, a functional blockage of VEGF, in the development of placenta is thought to be one of the major causes of repeated miscarriages in gestation. We then examined whether transfusion of VEGF-expressing extrinsic EPCs prevented frequent miscarriage via its promotional effect on neovascularization with a VEGF–eNOS signaling pathway in a mouse miscarriage model. The results showed that systemic EPC transfusion significantly reduced the rate of miscarriage, and EPCs were frequently observed in the miscarriage placenta. In contrast, only a few EPCs were detected in the placenta of normal gestation. The vascular pattern was irregular, and vessel size was small in the miscarriage placenta compared with that of normal gestation. The placental vascular pattern in miscarriage tended to be normalized with increased vessel size up to a similar level as normal gestation by EPC recruitment. For the mechanistic insight, since soluble Flt1 inhibits EPC functions, it was suggested that the increased soluble Flt1 could suppress the recruited EPC functional activity in the miscarriage placenta. In vitro experiments by soluble Flt1 treatment in cultured EPCs suggested that the vascular abnormality could be partly due to the inhibition of eNOS expression by the increased amounts of soluble Flt1. These findings from animal experiments indicated that autologous EPC therapy may be a novel therapy to prevent miscarriage in high-risk pregnancies, such as preeclampsia.